Hyper-Inflammatory Monocyte Activation Following Endotoxin Exposure in Food Allergic Infants - Neeland, Melanie R.; Novakovic, Boris; Dang, Thanh D.; Perrett, Kirsten P.; Koplin, Jennifer J.; Saffery, Richard (Frontiers in Immunology, 2020)
Several recent studies have reported a key role for innate cell hyper-responsiveness in food allergy. This has predominantly been observed in early life, with evidence that innate immune function may return to baseline if food allergy resolves in later childhood. Hallmarks of hyper-responsiveness include increased circulating frequency of monocytes and altered innate cell cytokine responses to in vitro exposure with bacterial endotoxin. These features mirror the defining signatures of trained innate immunity, seen in other complex diseases. In this study, detailed immune cell and cytokine profiling was performed on peripheral blood mononuclear cells at baseline from 27 1 year old infants in the HealthNuts cohort (n = 16 egg allergic and n = 11 non-allergic healthy controls) and following monocyte stimulation. We show that egg allergic infants have increased frequency of circulating monocytes, reduced numbers of regulatory CD4 T cells and increased monocyte: CD4 T cell ratios relative to healthy controls. Monocytes from both egg allergic and non-allergic infants responded to endotoxin stimulation with rapid cytokine production and downregulation of the surface receptor CD16, however monocytes from egg allergic infants were hyper-responsive, producing significantly more inflammatory cytokines (TNFα, IL-6, IL-1β, IL-8) and innate cell recruiting factors (MIP-1α) than healthy controls. This work indicates that monocytes of food allergic infants are programmed to a hyper-inflammatory phenotype and that the development of food allergy may be associated with trained immunity in early life.